Bariatric Surgery‐Induced Changes in Intima‐Media Thickness and Cardiovascular Risk Factors in Class 3 Obesity: A 3‐Year Follow‐Up Study. Issue 9 (9th August 2020) - Domenech‐Ximenos, Blanca; Cuba, Victor; Daunis‐i‐Estadella, Pepus; Thió‐Henestrosa, Santiago; Jaldo, Francisco; Biarnes, Carles; Molina, Xavier; Xifra, Gemma; Ricart, Wifredo; Bardera, Anton; Boada, Imma; Essig, Marco; et al.
Abstract : Objective: The impact of weight loss induced by bariatric surgery (BS) and nonsurgical approaches on cardiovascular risk factors (CVRFs) has not been fully elucidated. We assessed the effects of BS and a nonsurgical approach on carotid intima‐media thickness (CIMT) and CVRFs in participants with class 3 obesity. Methods: A total of 87 participants with obesity (59 women; 46 [37‐52] years old; BMI, 43 [40‐47]) and 75 controls were recruited; 21 (25%) participants with obesity underwent BS. BMI, blood pressure, cholesterol, triglycerides, fasting plasma glucose, C‐reactive protein, CIMT, and Framingham Risk Score were measured at baseline and at 3‐year follow‐up. Independent factors for reduction in CIMT were analyzed. The literature on the effects of BS and CIMT was reviewed. Results: After BS, BMI decreased from 45.45 to 27.28 ( P  < 0.001), and mean CIMT decreased from 0.64 mm (0.56‐0.75 mm) to 0.54 mm (0.46‐0.65) mm ( P  < 0.012), equivalent to 0.005 mm/kg of weight lost. At 3‐year follow‐up, participants who had undergone BS had similar CIMT and CVRFs to the control group. No changes in CVRFs were seen related to the nonsurgical approach. BMI reduction after BS had the strongest independent association with decreased CIMT. Conclusions: Weight loss after BS decreases CIMT and CVRFs in middle‐aged participants with class 3 obesity, resulting in CIMT similar to that observed in lean participants.